Tantangan Hukum dalam Regulasi Transaksi Kripto di Indonesia Antara Peluang dan Risiko - Laksito, Joni; Karisma, Dian; Hartono, Budi (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
This study analyzes the legal challenges and opportunities surrounding cryptocurrency regulation in Indonesia. With the rising popularity of digital assets, the Indonesian government has introduced a regulatory framework through the Commodity Futures Trading Regulatory Agency (BAPPEBTI), Bank Indonesia (BI), and the Financial Services Authority (OJK) to manage cryptocurrency trading and mitigate associated risks. The research uses a qualitative descriptive-analytical approach, examining primary data from regulatory documents and secondary data from international regulatory frameworks, to highlight the complexities of implementing an effective regulatory structure. Findings reveal that while Indonesia's restrictive regulations protect financial stability, they limit broader adoption and innovation in the digital economy. Comparisons with Japan and the European Union suggest that a more flexible regulatory approach could balance consumer protection with digital innovation. This study recommends public education and regulatory adaptation to respond dynamically to the fast-evolving cryptocurrency market.